2014
DOI: 10.3746/jkfn.2014.43.7.1112
|View full text |Cite
|
Sign up to set email alerts
|

Intake Status and Recognition of Health Functional Foods by Pre- and Post-Menopausal Women in Seoul and Gyeonggi Province

Abstract: The purpose of this study was to investigate intake status and recognition of health functional foods by pre-and post-menopausal women in Seoul and Gyeonggi province. Survey questions were administered to 400 women around menopausal period, and data analysis was completed using the SPSS window program. Thirty-three percent of women recognized that they are healthy, and 47.1% of respondents are concerned with maintaining their health. However, respondents showed a low level of knowledge about the definition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…After duplication removal, 461 studies remained, of which 85 studies were human studies and were assessed for eligibility. Fifty of these studies in the literature were unrelated to menopause and seven studies were about combinations or derivatives, four articles were cross-sectional studies (T.-H. Kim & Lee, 2016;Lee, 2004;Ozcan et al, 2019;Park et al, 2014), one of them has two versions, one was study design (Newton et al, 2005), and two were conference papers (Tahmasbi et al, 2015;Yarmohammadi & Abdi, 2015). We could not find the full texts of four related papers, and after contacting the authors several times, we got one full text (Huber et al, 2017) and did not get any response from others (Ahn et al, 2010;Mohajer & Abdi, 2014;Rouzbahani & Abdi, 2014).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…After duplication removal, 461 studies remained, of which 85 studies were human studies and were assessed for eligibility. Fifty of these studies in the literature were unrelated to menopause and seven studies were about combinations or derivatives, four articles were cross-sectional studies (T.-H. Kim & Lee, 2016;Lee, 2004;Ozcan et al, 2019;Park et al, 2014), one of them has two versions, one was study design (Newton et al, 2005), and two were conference papers (Tahmasbi et al, 2015;Yarmohammadi & Abdi, 2015). We could not find the full texts of four related papers, and after contacting the authors several times, we got one full text (Huber et al, 2017) and did not get any response from others (Ahn et al, 2010;Mohajer & Abdi, 2014;Rouzbahani & Abdi, 2014).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Several studies have investigated the factors contributing to functional food or dietary supplement intake, mainly focusing on gender, age, socioeconomic factors, and health status ( 11 23 ). Although the results are not generalizable ( 11 , 12 ), and are even somewhat contradictory ( 13 , 22 , 23 ), women, older adults, and those with higher levels of education and income were more likely to consume functional foods or dietary supplements ( 14 18 ). Health-conscious people committed to managing their health, such as through physical activity or healthy eating, were more likely to consume functional foods or dietary supplements ( 16 , 18 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Health-related factors such as having disability and chronic diseases, having being admission, and physician visits were significantly associated with dietary supplement consumption ( 22 ). Park et al revealed that educational level critically influenced dietary supplement intake among menopausal women ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…When looking into previous research regarding middle-aged women's preparation for senescence [8] , the quantitative research utilized comparisons between generations or adults generally for research participants [9] . Moreover, there has been research focusing on successful aging awareness and comparing it with acts to improve health [10] , research on identifying the influence of health condition or self-esteem affecting the expectations of aging [4] , and researches on the actual conditions of women's intake of health functional food before and after menopause [11] . The qualitative research contains an awareness of successful aging [12] and research on the adaptation and changes in a mother's role performance [13] .…”
Section: Introductionmentioning
confidence: 99%